2020
DOI: 10.1021/acssuschemeng.0c04981
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Cascades toward Aliphatic Nitriles Starting from Biorenewable Feedstocks

Abstract: A modern concept of producing nitriles involves aldoxime dehydratases, which are capable of dehydrating aldoximes to the corresponding nitriles without need of a cofactor. Aldoximes as the starting material for nitrile synthesis are easily prepared by condensation of hydroxylamine with the corresponding aldehydes. In this contribution we present chemoenzymatic cascade reactions toward nitriles consisting of an initial nitroxyl radical-catalyzed oxidation of aliphatic alcohols to aldehydes using sodium hypochlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Whole cell preparations have successfully been utilised in flow, demonstrating the versatility of these enzymes. [308][309][310] 2.3.2 Oxidation reactions 2.3.2.1 Alcohol oxidation to aldehydes. Enzyme-catalysed alcohol oxidation to aldehydes, relevant compounds for the flavour and fragrance industry, can be carried out by the classic nicotinamide-dependent alcohol dehydrogenases (ADHs).…”
Section: Synthesis Of Esters and Amides In Watermentioning
confidence: 99%
“…Whole cell preparations have successfully been utilised in flow, demonstrating the versatility of these enzymes. [308][309][310] 2.3.2 Oxidation reactions 2.3.2.1 Alcohol oxidation to aldehydes. Enzyme-catalysed alcohol oxidation to aldehydes, relevant compounds for the flavour and fragrance industry, can be carried out by the classic nicotinamide-dependent alcohol dehydrogenases (ADHs).…”
Section: Synthesis Of Esters and Amides In Watermentioning
confidence: 99%
“…This may provide improved environmental metrics due to the wastewater associated with the downstream when DMSO is removed [ 8 , 9 ]. In a more recent work, the concept has been further extended by starting with alcohols as biogenic raw materials and performing the ((2,2,6,6-Tetramethylpiperidin-1-yl)-oxyl) TEMPO-mediated oxidation, oxime formation, and biocatalytic step involving aldoxime dehydratases [ 33 ]. As in previous cases, a careful optimization of the multi-step approach was needed to secure that the different catalysts are not deactivated and that compatible conditions are found.…”
Section: Toward the Production Of Bulk Chemicals And Biorefinery-like Approaches Using Aldoxime Dehydratasesmentioning
confidence: 99%
“…We previously reported that CAR biocatalysts retain their activity, when exposed to water-immiscible organic solvents like nheptane or biocompatible nhexadecane for ISPR, 26,27 but little was known about co-solvent effects of these solvents on Oxds. Previous studies with different Oxds reported on (di)nitrile products as second layer to achieve exceptional product titers in oxime dehydration reactions, 32 which hints towards organic solvent tolerance of Oxds. 32 To verify this assumption, immiscible organic solvents previously selected for aldehyde production 26 were examined as media in the oxime dehydration step.…”
mentioning
confidence: 97%
“…Previous studies with different Oxds reported on (di)nitrile products as second layer to achieve exceptional product titers in oxime dehydration reactions, 32 which hints towards organic solvent tolerance of Oxds. 32 To verify this assumption, immiscible organic solvents previously selected for aldehyde production 26 were examined as media in the oxime dehydration step. At the same time, the robustness of OxdBr1 towards oxygen was assessed because the reactions were carried out in tubes with a large headspace of air.…”
mentioning
confidence: 97%